2019
DOI: 10.3390/jfmk4020027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Specific Aquatic Program on Social and Gross Motor Skills in Adolescents with Autism Spectrum Disorders: Three Case Reports

Abstract: Swimming pool activities revealed to be efficacious to train psychomotor skills and increase adaptive behaviors in children with Autism Spectrum Disorders (ASD). Therefore, the purpose of this study was to investigate the efficacy of a specific multi-systemic aquatic therapy (CI-MAT) on gross motor and social skills in three adolescents with Autism Spectrum Disorders (ASD). Methods: three adolescents with ASD of which two boys (M1 with a chronological age of 10.3 years and a mental age of 4.7 years; M2 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
2
28
0
3
Order By: Relevance
“…According to Tucker's observations (2016), children or/and adolescents with ASD who participated in aquatic actions had the possibility for significant learning, allowing the experience to encourage, to develop and start with a deep understanding of the situation from the 'opposite' point of view. Some activities which were used to measure social and emotional integration and interdependence by Battaglia (2019) showed that aquatic techniques have benefits for participants with ASD because it reflects the real-life as a model to their playing. In this research, the effect of aquatic activities agrees with one more study which had the same target.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Tucker's observations (2016), children or/and adolescents with ASD who participated in aquatic actions had the possibility for significant learning, allowing the experience to encourage, to develop and start with a deep understanding of the situation from the 'opposite' point of view. Some activities which were used to measure social and emotional integration and interdependence by Battaglia (2019) showed that aquatic techniques have benefits for participants with ASD because it reflects the real-life as a model to their playing. In this research, the effect of aquatic activities agrees with one more study which had the same target.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies collected data using an observation schedule (Battaglia et al, 2019;Primenta et al, 2016;Tucker, 2016) with a video recording of the sessions. Data were scored according to a scale which aimed to identify the number of components of each skill or behavior, the participants completed independently.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations